2020
DOI: 10.32505/jades.v1i2.3031
|View full text |Cite
|
Sign up to set email alerts
|

Instagram as A Media to Enhance Writing Skill of Students in Langsa

Abstract: This research is carried out to investigate how the uses of Instagram application to improve students’ writing skill. The participant of this research is three students of seventh semester from English Department of IAIN Langsa in academic Years 2020/2021 who have been selected through purposive sampling based on certain characteristics. In here, there are 3 students. This research used qualitative method to gain the data; observation and documentation. Based on the results, they used Instagram features; photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this section, the findings obtained from the analysis of research data on utilizing Instagram to improve the vocabulary of eighth grade students of Junior High School. Instagram is the most popular way to learn vocabulary in the experimental class and without Instagram (Live learning) for the control class (Nurmala Sari & Afrida, 2020;Pujiati et al, 2019;Sari & Wahyudin, 2019). While there may not have been any previous studies that statistically reported the effectiveness of instagram as a student vocabulary learning medium, which collectively support the notion that instagram is an effective application for improving students ' vocabulary skills.…”
Section: Findings and Discussionmentioning
confidence: 92%
“…In this section, the findings obtained from the analysis of research data on utilizing Instagram to improve the vocabulary of eighth grade students of Junior High School. Instagram is the most popular way to learn vocabulary in the experimental class and without Instagram (Live learning) for the control class (Nurmala Sari & Afrida, 2020;Pujiati et al, 2019;Sari & Wahyudin, 2019). While there may not have been any previous studies that statistically reported the effectiveness of instagram as a student vocabulary learning medium, which collectively support the notion that instagram is an effective application for improving students ' vocabulary skills.…”
Section: Findings and Discussionmentioning
confidence: 92%